Direct threshing of paddy (Oryza sativa) ear-head with reduced straw and optimized grain throughput rate - SHEKHAR KUMAR SAHU; ALPNA DUBEY (The Indian Journal of Agricultural Sciences, 2024)
Reduction of the straw intake is a new harvesting technique that reduces energy and input costs. In existing combine harvesters, the cutter bar of the standard header is set at an increased height, or the stripper header combine harvester is used to minimize the straw intake. The thresher was developed and tested in the year 2018 and 2019, at Indian Institute of Technology, Kharagpur, West Bengal to reduce the straw intake by direct ear head threshing of standing plants. It reduces energy consumption compared to some common existing harvesting methods. The specially designed plant guiding plates were accommodated before the threshing cylinder to achieve this. The set of two guiding plates passes over the plant’s row and converges the panicle portion of plants by bending them gradually. The rice (Oryza sativa L.) panicles were placed over the rotating cylinder and the stem portion remains in a standing posture. Thus, only 4.16% of total straw available on the plants was fed, and about 23 times straw intake was reduced. RSM-based response surface methodology was used to design the experiment. During the experiment, the grain throughput rate (GTR) was varied by changing the speed of plant feeding. To measure the cylinder speed, threshing torque, and plant feed speed the laboratory model thresher was equipped with rotary encoder, torque transducer and proximity sensors, respectively. The collected threshed mixture was analyzed to determine threshing performance. The optimized GTR and cylinder speed were 180 kg/h and 17.55 m/sec at which the threshing efficiency, total grain loss, and specific energy were 98.36%, 4.67%, and 1.1 kWh/t of grain, respectively.